2022
DOI: 10.1177/09603271221106344
|View full text |Cite
|
Sign up to set email alerts
|

Withania somnifera (Ashwagandha) root extract counteract acute and chronic impact of γ-radiation on liver and spleen of rats

Abstract: The exposure to ionizing radiation has become inescapably because of increased dependence on radiation to execute works in different fields and also its influences on biological systems. Thus, the current study aimed at examination of the radio-protective effect of the natural ashwagandha (Ag) against acute and chronic doses of γ-radiation on liver and spleen of rats. The impact of Ag was inspected in rats exposed to acute exposure of 8 Gy (single dose) or to chronic exposure of 8 Gy (2 Gy every other day for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…The present study found that exposing arthritic rats to fractionated whole body γ-irradiation (2 Gy/fraction for four consecutive weeks; A + R group) led to marked deterioration in the clinical arthritic signs, biochemical indices of oxidative stress and inflammation in liver, kidney, lung, and heart tissues ( Figure 5 ), in addition to degenerative lesions in the ankle joints which are in line with the study of Thabet et al 73 The observed results may be ascribed to an excessive generation of reactive oxygen species (ROS). This generates oxidative damage to biomolecules, linked to the synthesis of pro-inflammatory mediators.…”
Section: Discussionsupporting
confidence: 92%
“…The present study found that exposing arthritic rats to fractionated whole body γ-irradiation (2 Gy/fraction for four consecutive weeks; A + R group) led to marked deterioration in the clinical arthritic signs, biochemical indices of oxidative stress and inflammation in liver, kidney, lung, and heart tissues ( Figure 5 ), in addition to degenerative lesions in the ankle joints which are in line with the study of Thabet et al 73 The observed results may be ascribed to an excessive generation of reactive oxygen species (ROS). This generates oxidative damage to biomolecules, linked to the synthesis of pro-inflammatory mediators.…”
Section: Discussionsupporting
confidence: 92%
“…The anti-inflammatory effect of ASH demonstrated in our study comes in co-ordinance with Azab et al (17) who reported that ashwagandha produced a significant reduction in level of inflammatory markers (IL-17, IL-10, and α7-nAchR) and oxidative stress markers (MDA, GSH, and ROS) in spleen and liver tissues of rats treated with ASH and exposed to γ-radiation, and Elhadidy et al (30) who proved that ashwagandha extract produced anti-inflammatory and anti-oxidant effects against aluminum chloride (AlCl 3 )-induced neurotoxicity in rats, the pretreatment with ASH extract counteracted the significant rise in TNF-α, MDA and NO levels induced by AlCl 3 to nonsignificant changes as compared with the control group.…”
Section: Discussionsupporting
confidence: 89%
“…• ASH: rats were administered 300 mg/kg b.w. (17) of Ashwagandha root extract by oral gavage for 8 successive days interrupted with injection of 0.5 ml saline on day 4 of experiment.…”
Section: Experimental Designmentioning
confidence: 99%
“…54 In addition, it was found in our recently published research paper that Ashwagandha protect normal cells from the hazardous effect of acute and chronic radiation because of its antioxidants and anti-inflammatory capabilities. 55 However, we believed that further insightful future investigations focusing on a diverse mediator involved in autophagy and necroptosis could be with benefit to decipher this discrepancy emerged and could disclose the exact mechanism of WS.…”
Section: Discussionmentioning
confidence: 99%